Performance evaluation of the CDN1 altimetry Cal/Val transponder to internal and external constituents of uncertainty. Issue 8 (15th October 2022) - Mertikas, Stelios P.; Donlon, Craig; Mavrocordatos, Constantine; Piretzidis, Dimitrios; Kokolakis, Costas; Cullen, Robert; Matsakis, Demetrios; Borde, Franck; Fornari, Marco; Boy, Francois; Tripolitsiotis, Achilles; Guinle, Thierry; et al.
Abstract: A microwave range transponder has been operating at the CDN1 Cal/Val site on the mountains of Crete for about 6 years, to calibrate international satellite radar altimeters in the Ku-band. This transponder is part of the European Space Agency Permanent Facility for Altimetry Calibration, and has been producing a continuous time series of range biases for Sentinel-3A, Sentinel-3B, Jason-2, Jason-3 and CryoSat-2 since 2015. As of 18-Dec-2020, the CDN1 transponder has allowed calibration of the new operational altimeter of Sentinel-6 MF satellite as it flies in tandem with Jason-3. This work investigates range biases derived from the long time series of Jason-3 (and subsequently that of Sentinel-6 MF since both follow the same orbit) and tries to isolate systematic and random constituents in the produced calibration results of the transponder. Systematic components in the dispersion of transponder biases are identified as of internal origin, coming from irregularities in the transponder instrument itself and its setting, and of external cause arising from the altimeter, satellite orbit, Earth's position in space, geodynamic effects and others. Draconic harmonics, principally the 58-day period, play a significant role in the transponder results and create cyclic trends of maximum amplitude of 17 mm at times in the calibration results. The attitude of the satellite body as it changes for solar panel orientation contributes an offset of about 7 mm when yaw rotation is off its central position, and the atmospheric, water mass and non-tidal ocean loadings are responsible for an annual systematic signal of 10 mm. At the time of writing, all other constituents of uncertainty seem random in nature and not significantly influential, although humidity requires further investigation in relation to the final transponder calibration results.